Sejarah Penyebaran Islam di Konfederasi Turatea Abad XVII (Tinjauan Sistem Pemerintahan dan Religi) - Eka Yuliana Rahman (Jurnal Pendidikan Sejarah, 2020)
This study aims to examine the history of Islamization in the Turatea Confederation, a review of the government and religious systems, especially in the XIII Century. This research is based on a note from Christian Pelras, Anthropologist of the Bugis-Makassar, said that before the Gowa-Tallo kingdom made Islam a royal religion, the ruler (aristocrats) and the people of the Turatea Confederation had embraced Islam through the practice of power relations between the kingdom, religious leaders and the people . This study uses qualitative methods to find and describe in analysis and interpret the socio-cultural conditions of the people in the Turatea Confederation before and after Islam. The results show that the pattern of power distribution centered on figures as local authorities is the most effective means of spreading religious teachings. The development of Islamic religious symbols changed the system of government and belief by strengthening the Islamic tradition in the Turatea Confederation. Tulisan ini bertujuan untuk menelaah sejarah Islamisasi di Konfederasi Turatea dalam tinjuan sistem pemerintahan dan religi khususnya pada Abad XIII. Riset ini didasari oleh adanya catatan dari Christian Pelras, Antropolog kajian kebudayaan Bugis-Makassar menyebutkan, sebelum kerajaan Gowa-Tallo menjadikan Islam agama kerajaan, penguasa (bangsawan) dan rakyat Konfederasi Turatea telah menganut Islam melalui praktik relasi kekuasaan antara kerajaan, tokoh agama dan rakyat. Riset ini menggunakan metode kualitatif untuk menemukan dan mendeskripsikan secara analisis serta menginterpretasikan kondisi sosial budaya masyarakat di Konfederasi Turatea sebelum dan sesudah Islam. Hasilnya menunjukkan, pola distribusi kekuasaan yang berpusat pada figur sebagai penguasa lokal merupakan sarana paling ampuh menyebarkan ajaran agama. Perkembangan syiar agama Islam mengubah sistem pemerintahan dan kepercayaan dengan makin menguatnya tradisi Islam di Konfederasi Turatea.